Mechanical and Durability Studies about the use of Municipal Solid Waste Landfill in Concrete - Nair, Arya R.; Nirmala, D.B. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Landfilling is the most common and cheapest method of waste management practice in India. Municipal Solid Waste Landfills (MSWL) became a nuisance affecting the health, hygiene, sanitation and aesthetics of the surrounding area. Aggregates occupy almost 70% of concrete, so replacing waste materials with them could be a rewarding choice.
Keywords: concrete production; sustainable concrete; municipal solid waste landfill; aggregate replacement; strength; mechanical properties